A REVIEW ON - SOLAR CONCENTRATORS, PERFORMANCE OF SOLAR COLLECTORS & ENERGY STORAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Parabolic trough concentrators are one type of concentrators which reflects the sunlight on the receiver (Line type) and gives us wet steam for water. It can be tried with any type of fluid. Presently solar collectors are used for residential and commercial use. These solar collectors require high maintenance and high installation cost, solar concentrators help us in these disadvantages. This review paper concentrates on solar concentrators and various fluids that can be used in receiver. It also focuses on surface shape measurement of solar concentrator in solar thermal power application. In order to capture maximum amount of solar energy it is required to orient the concentrator as per the position of the sun i.e. tracking is required .However some of the concentrators do not track and are referred as fixed concentrators. The objective of the project is to track the receiver instead of solar concentrator.